2010
DOI: 10.1111/j.1464-410x.2009.09052.x
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar transurethral resection of the prostate causes less bleeding than the monopolar technique: a single‐centre randomized trial of 202 patients

Abstract: and after surgery was measured using a photometer. Other variables compared included indices of resection speed and transfusion rate. RESULTSThere were no statistically significant differences in operative duration, resection weight, resection speed or radicality of resection. However, the median blood loss was 235 mL for the bipolar and 350 mL for monopolar TURP ( P < 0.001). The decrease in blood haemoglobin concentration during the day of surgery was smaller in the bipolar group (5.5% vs 9.6% P < 0.001). Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
57
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 22 publications
8
57
1
Order By: Relevance
“…4,6 In addition, Mamoulakis and associates 15 performed a subgroup analysis focused on a bipolar device, the PlasmaKinetic system, and detected an improved safety benefit regarding transfusion. One 16 of six RCTs regarding the TURis system [16][17][18][19][20][21] and no trials regarding the Vista system 22 or AUTOCON II 400 system 23 showed significant differences for transfusion. As theoretical support, some ex vivo experiments have shown that a bipolar current has the nature of deep coagulation and a ''cut-and-seal'' property.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,6 In addition, Mamoulakis and associates 15 performed a subgroup analysis focused on a bipolar device, the PlasmaKinetic system, and detected an improved safety benefit regarding transfusion. One 16 of six RCTs regarding the TURis system [16][17][18][19][20][21] and no trials regarding the Vista system 22 or AUTOCON II 400 system 23 showed significant differences for transfusion. As theoretical support, some ex vivo experiments have shown that a bipolar current has the nature of deep coagulation and a ''cut-and-seal'' property.…”
Section: Discussionmentioning
confidence: 99%
“…Many RCTs have reported that the postoperative serum sodium changes were smaller in the B-TURP arm. 6,16,18 Theoretically, this B-TURP nature of less influence on the mineral balance can also provide benefit for the cardiopulmonary circulation, although there is no evidence to show that B-TURP reduces some rare but life-threatening adverse events, such as cardiac or pulmonary failure.…”
mentioning
confidence: 99%
“…In previous work, we have found that blood loss is significantly lower using the bipolar technique. 1 Concerning the higher degree of vaporization, this difference is even greater than reported, as further 50% more tissue is removed when using the bipolar resection instrument as compared with the monopolar. An estimate indicates that the blood loss would then be as low as 6 mL/g resected tissue, which is far below any former reported value of TURP-associated bleeding in previous series of both bipolar and monopolar resection.…”
Section: Discussionmentioning
confidence: 86%
“…1,2,11,12 The bipolar technique is superior in terms of blood loss and reduces-or eliminates-the risk of the classical TUR-syndrome. When assessing the quality of histologic specimens from resected tissue, it has also been shown that the coagulation artefacts of the chips are less than in the ones provided by monopolar resection, thus facilitating a more accurate pathologic diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation